2006
DOI: 10.1007/s00402-006-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Void filling of tibia compression fracture zones using a novel resorbable nanocrystalline hydroxyapatite paste in combination with a hydroxyapatite ceramic core: first clinical results

Abstract: The use of the Ostim and Cerabone combination is an effective method in treating tibia compression fractures with large defect zones left after reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…On the other hand, a >10% increase of nHA reduces the mechanical properties due to a marked clustering effect of nano-particles [5]. The chemical formula of HA is Ca 10 (PO 4 ) 6 (OH) 2 and it is known as pentacalcium hydroxide tris (orthophosphate) [6][7][8]. In the last twenty years, enormous attention has been given to the HA-based filler reinforcement for polymer matrices for plausible biomedical applications such as tissue engineering [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a >10% increase of nHA reduces the mechanical properties due to a marked clustering effect of nano-particles [5]. The chemical formula of HA is Ca 10 (PO 4 ) 6 (OH) 2 and it is known as pentacalcium hydroxide tris (orthophosphate) [6][7][8]. In the last twenty years, enormous attention has been given to the HA-based filler reinforcement for polymer matrices for plausible biomedical applications such as tissue engineering [9].…”
Section: Introductionmentioning
confidence: 99%
“…This ready-to-use injectable paste received CE (Conformite Europeenne) approval in 2002. Ostim® is a suspension of synthetic nanocrystalline HA (average crystal dimensions: 100 × 20 × 3 nm3 (a needle-like appearance); specific surface area ~ 100 m2/g) in water, prepared by a wet chemical reaction [610]. After completion, the HA content in the paste is ~ 35%.…”
Section: Bone Repairmentioning
confidence: 99%
“…Ostim® can be used in metaphyseal fractures and cysts, alveolar ridge augmentation, acetabulum reconstruction and periprosthetic fractures during hip prosthesis exchange operations, osteotomies, filling cages in spinal column surgery, etc. [609][610][611][612][613][614][615][616][617][618][619][620][621][622]. It might be incorporated into bones and a new bone formation is visible after only three months [623].…”
Section: Bone Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A further series by the same group showed similarly encouraging results when it was used to treat metaphyseal defects in fractures of the tibial plateau. 32 Nanocomposite scaffolds composed of type I collagen and nanostructured HA are currently being used in the treatment of osteochondral defects of the knee. Kon et al 33 have shown encouraging short-term clinical and radiological results with a nanocomposite biological implant for the treatment of focal osteochondral lesions.…”
Section: Orthopaedic Applicationsmentioning
confidence: 99%